2020
DOI: 10.1177/1055665620931707
|View full text |Cite
|
Sign up to set email alerts
|

Oronasal Fistula Risk After Palate Repair

Abstract: Objective: To assess risk factors for oronasal fistula, including 2-stage palate repair. Design: Retrospective analysis. Setting: Tertiary children’s hospital. Patients: Patients with non-submucosal cleft palate whose entire cleft repair was completed at the study hospital between 2005 and 2013 with postsurgical follow-up. Interventions: Hierarchical binary logistic regression assessed predictive value of variables for fistula. Variables tested for inclusion were 2 stage repair, Veau classification, sex, age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(42 reference statements)
1
15
0
1
Order By: Relevance
“…We observed a palatal fistula rate of 38% in our patient cohort and while the majority were asymptomatic, 14% nonetheless required operative repair. This rate is consistent with the oronasal fistula rates reported in the literature for both the PRS, [21][22][23][24][25][26] as well as the isolated CP patient populations, [27][28][29][30][31][32] and does not suggest that the MDO intervention makes the cleft more favorable morphologically for closure.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a palatal fistula rate of 38% in our patient cohort and while the majority were asymptomatic, 14% nonetheless required operative repair. This rate is consistent with the oronasal fistula rates reported in the literature for both the PRS, [21][22][23][24][25][26] as well as the isolated CP patient populations, [27][28][29][30][31][32] and does not suggest that the MDO intervention makes the cleft more favorable morphologically for closure.…”
Section: Discussionsupporting
confidence: 90%
“…The primary outcome of cleft palate repair lies in the achievement of velopharyngeal competence without fistula. [4][5][6][7][8][9][10][11][12][13][14] Of our 19 patients, one patient (with Veau classifications of III) had postoperative oronasal fistulas. The patient did not require further surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In all, the rates of VPI within our cohort were lower than those reported in the literature. [4][5][6][7][8][9][10][11][12][13][14] In fact, Sullivan et al conducted a 29-year analysis of patients undergoing palatoplasty, and found that of 449 patients, 85.1% had postoperative VPI. 5 The study also found significant correction between the incidence of VPI and increased Veau hierarchy and age at the time of palatoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been associated with ONF development after primary repair of a cleft palate. Outcomes are dependent on the type and timing of surgical repair, age at repair, surgeon and surgeon's volume, Veau classification, and cleft width [4][5][6]. Though a two-staged repair is primarily performed to minimize the impact on maxillary growth [7], several studies have shown it to be a significant risk factor for fistula formation [5,6,8].…”
Section: Risk Factorsmentioning
confidence: 99%